ALTERNATIVE NUMERAIRES FOR MEASURING WELFARE CHANGES: REVIEW OF EMPIRICAL ENVIRONMENTAL VALUATION STUDIES - Solikin, Akhmad (PLANNING MALAYSIA, 2021)
This study examines numeraire or an account unit that measures household welfare changes. Although money metric usually determines budget constraint, textbook explanations of the alternative metrics are limited. Therefore, the study aimed to fill the existing gap by systematically and qualitatively analysing previously published articles on environmental valuation in developing countries. The results showed the existence of alternative numeraires in working time, commodities, and financing. The alternative metrics are useful in the valuation of environmental goods and services in developing countries, especially those involving poor respondents and underdeveloped monetary transactions. The nonmonetary payments reduce zero bids due to the inability of subsistence people to pay in cash and help the poor express their true environmental values.